Practical Regional Cultural Values in Forming Student Character in Primary Schools in Central Aceh Regency: Practical Regional Cultural Values in Forming Student Character in Primary Schools in Central Aceh Regency - Muharramsyah, Rambang; Fitrah, Hariki (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
This research aims to explore the praxis of regional cultural values in the student character formation of Primary schools in Central Aceh Regency. The methodology in this research is qualitative research with an ethnographic approach. The research was conducted at three Central Aceh Regency schools: State Elementary School 7 Atu Lintang, State Elementary School 6 Bebesen, and State Elementary School 10 Kuta Panang. Data was collected through observation, interviews, and documentation. The informants in this research consisted of school principals, teachers, and students. Data analysis was carried out through domain, taxonomic, componential, and cultural theme analyses. The results of the research show that several forms of regional culture are developed in schools in forming student character, namely (1) at State Elementary School 7 Atu Lintang; wear traditional clothing or Karawang Gayo every Thursday, (2) at State Elementary School 6 Bebesen: use local language or Gayo every Thursday, both in learning activities and outside class hours, (3) at State Elementary School 10 Kuta Panang; emphasizes the character values that exist in a society which are developed in school life such as semayang gemesih, tertib and setie.